Silent Love: The Representation and Construction of Mumu’s Identity as the Child of a Deaf-Mute Father in the Film Mùmù - Amanda Nayoan; Muhammad Farhan Masrur (International Journal Labs, 2026)
Films play an important role in shaping public understanding of disability and family identity through visual and emotional representation. However, studies discussing children’s identity construction within families with disabilities, particularly deaf-mute families, remain limited. This research aims to analyze the representation of a deaf-mute family and the construction of Mùmù’s identity as the child of a deaf-mute father in the film Mùmù. The study also examines the influence of social groups on the formation of the child’s personal identity. This research employed a qualitative descriptive method using scenes, dialogues, gestures, visual elements, and cinematographic techniques as primary data sources. The analysis applied Stuart Hall’s representation theory, Murray Bowen’s family systems theory, and Tajfel’s social identity theory. Data collection was conducted through observation, documentation, and scene classification from the film. The findings reveal that the film represents deaf-mute families in a humane and emotional manner through non-verbal communication, warm lighting, close-up framing, and visual symbolism that emphasize affection and emotional attachment between father and child. Furthermore, family interaction patterns significantly shape Mùmù’s identity through self-differentiation, family projection, and relational triangles. Social identity processes, including self-categorization and social comparison, also influence Mùmù’s perception of himself within both deaf and hearing communities. In conclusion, the film demonstrates that disability is not merely a limitation but also a meaningful space for identity formation, emotional growth, and social belonging.